On Discrete-Continuous Modelling of the Railway Bogie and the Track for the Medium Frequency Dynamic Analysis - T. Szolc (Engineering Transactions, 2015)
In the present paper, the dynamic interaction between a bogie of a modern railway passenger car and a track is considered with the aid of a discrete-continuous mechanical model. This model enables us to investigate the bending-torsional-axial vibrations of the wheelsets coupled with the vertical and lateral vibrations of the track through the wheel-rail contact forces. The numerical results are obtained in the form of natural frequencies, eigenfunctions and frequency response functions for the linearized bogie-track system as well as in the form of time histories and corresponding amplitude spectra of forced vibrations obtained by means of computer simulation performed for the non-linear system. In the computational examples for the bogie-track interaction, the influence of static and dynamic properties of several kinds of the track on the system dynamic response is studied.